Host specificity in parasitic plants—perspectives from mistletoes. (18th August 2015) - Okubamichael, Desale Y.; Griffiths, Megan E.; Ward, David
Abstract : Mistletoes are very fascinating parasitic plants. For centuries, people have been kissing under mistletoes during Christmas celebrations. Unlike most common plants, mistletoes grow on the branches of other plants and rely on these "host" plants for water and nutrients. Scientists have been trying to understand why parasitic plants differ in the number of host species parasitised. Like many parasitic plants, mistletoes can parasitise several plant species or only use one or far fewer species. This review contributes to the current broad understanding of parasite-host interactions using mistletoe as a case study. Future research needs are also highlighted. Abstract: Host specificity has been investigated for centuries in mistletoes, viruses, insects, parasitoids, lice and flukes, yet it is poorly understood. Reviewing the numerous studies on mistletoe host specificity may contribute to our understanding of these plants and put into context the dynamics at work in root parasitic plants and animal parasites. The mechanisms that determine host specificity in mistletoes are not as well documented and understood as those in other groups of parasites. To rectify this, we synthesized the available literature and analyzed data compiled from herbaria, published monographs and our own field studies in South Africa. As for other groups of parasites, multiple factors influence mistletoe host specificity. Initially, pollination affects gene flow. Subsequently, seed dispersal vectors (birds and marsupials), host abundance and compatibility (genetic, morphological, physiological and chemical), history and environmental conditions affect the interaction of mistletoes and their hosts and determine host specificity. Mistletoe–host network analyses and a geographic mosaic approach combined with long-term monitoring of reciprocal transplant experiments, genetic analyses of confined mistletoe populations and comparative phylogenetic studies could provide further insights to our understanding of host specificity. Some of these approaches have been used to study animal–plant interactions and could be adopted to test and evaluate host specificity in mistletoes at local and larger geographic scales.